Transient Hepatic Overexpression of Insulin-Like Growth Factor 2 Induces Free Cholesterol and Lipid Droplet Formation - Kessler, Sonja M.; Laggai, Stephan; Van Wonterghem, Elien; Gemperlein, Katja; Müller, Rolf; Haybaeck, Johannes; Vandenbroucke, Roosmarijn E.; Ogris, Manfred; Libert, Claude; Kiemer, Alexandra K. (Frontiers in Physiology, 2016)
Although insulin-like growth factor 2 (IGF2) has been reported to be overexpressed in steatosis and steatohepatitis, a causal role of IGF2 in steatosis development remains elusive. Aim of our study was to decipher the role of IGF2 in steatosis development. Hydrodynamic gene delivery of the Igf2 plasmid used for transient IGF2 overexpression employing codon-optimized plasmid DNA resulted in a strong induction of hepatic Igf2 expression. The exogenously delivered Igf2 had no influence on endogenous Igf2 expression. The downstream kinase AKT was activated in IGF2 animals. Decreased ALT levels mirrored the cytoprotective effect of IGF2. Serum cholesterol was increased and sulfo-phospho-vanillin colorimetric assay confirmed lipid accumulation in IGF2-livers without signs of inflammation. Interestingly, hepatic cholesterol and phospholipids, determined by thin layer chromatography and free cholesterol by filipin staining, were specifically increased. Lipid droplet (LD) size was not changed, but their number was significantly elevated. Furthermore, free cholesterol, which can be stored in LDs and has been reported to be critical for steatosis progression, was elevated in IGF2 overexpressing mice. Accordingly, HmgCoAR was upregulated. To have a closer look at de novo lipid synthesis we investigated expression of the lipogenic transcription factor SREBP1 and its target genes. SREBP1 was induced and also SREBP1 target genes were slightly upregulated. Interestingly, the expression of Cpt1a, which is responsible for mitochondrial fatty acid oxidation, was induced. Hepatic Igf2 expression induces a fatty liver, characterized by increased cholesterol and phospholipids leading to accumulation of LDs. We therefore suggest a causal role for IGF2 in hepatic lipid accumulation.